Literature Review on Korean Medicine Treatment for Alopecia - Seul Woo Leem; Min Kyeong Kim; Seo Lim Ko; Hye In Jeong; Kyeong Han Kim (Korean Pharmacopuncture Institute, 2021)
This study aimed to analyze the use of Korean medicine treatments for alopecia in among clinical studies. We identified and analyzed 22 studies from Korean databases; Oriental Medicine Advanced Searching Integrated System (OASIS), Science ON, Korean Studies Information Service System (KISS), and Research Information Sharing Service (RISS) and international database; PubMed. We analyzed the Korean medical treatment in each case and determined the tendency to use each intervention. We analyzed 1,464 patients from 22 selected studies. Herbal medicine, acupuncture, external medicine or products, pharmacopuncture, and phototherapy were used for alopecia treatment. The herbal medicines mainly used to treat alopecia were Gagam Cheongyoung-tang, Gagam Hwajung-hwan, and Yukmijihwang-tang·hwan. The acupoints primarily used were GV20, EX-HN1, GB5, KI3, PC6, ST36, GV22, and A-shi. The most commonly used pharmacopuncture therapies were Hwangryunhaedoktang (HH), Carthami Fructus (CF), Bee Venom (BV), and Hominis placenta (HP). The Korean medical treatment for alopecia improved the condition of patients. However, seven studies reported the occurrence of side effects such as pruritus, dazed, drowsiness, headache, pain, and diarrhea. This study shows the potential of Korean medicine for the treatment of alopecia. Further studies with a large sample size and long-term follow-up are warranted to establish the primary treatment guidelines and objective out-come measures for alopecia.